Hearts and minds [videorecording (DVD)] - Davis, Peter, 1937- (Criterion collection, 2002)
Examines the American involvement in Vietnam, and is a chronicle of the war from a psychological perspective. Includes interviews with General William Westmoreland, former Secretary of Defense Clark Clifford, Senator William Fulbright, Walt Rostow, and Daniel Ellsberg, as well as American Vietnam veterans and Vietnamese leaders. Presidents Truman, Kennedy, Johnson, and Nixon are shown in rare footage.